133k views
0 votes
How do I solve this equation and check the solutions?

How do I solve this equation and check the solutions?-example-1
User Mohan Ram
by
5.5k points

1 Answer

5 votes

Answer:

{-6}

Explanation:

Step 1 Raise both sides of the equation to the index of the radical in the case 2


(√(2x+13) )^(2) =(x+7)^(2)


2x + 13 = (x+7)(x+7)


2x +13 = x^(2) + 14x + 49\\0=x^(2) +12x+36

Step 2 Factor

(x + 6)(x + 6) = 0

x + 6 = 0

x = - 6

Step 3 Check -6


√(2(-6)+13) = -6 + 7\\√(-12+13) = 1\\√(1) = 1\\1 = 1

User Rosario Russo
by
5.3k points